Do no.11 plzz .It's AP of class 12 maybe...
Attachments:
Answers
Answered by
3
★ Hi , there !!! ★
here is your answer !!
we have to calculate the ratio of nth term =>
and the , given ratio is => ( 2n + 3 ) : (5n -7 )
now , replace the value of of n by 2n - 1
we get ,
{ 2 × ( 2n - 1 ) + 3 } : { 5 × ( 2n + 1 ) - 7 }
=>( 4n + 2 - 3 ) : ( 10n - 5 -7 )
=>( 4n - 1) : ( 10n - 12 )
hope it helps you dear !!
thanks !!
here is your answer !!
we have to calculate the ratio of nth term =>
and the , given ratio is => ( 2n + 3 ) : (5n -7 )
now , replace the value of of n by 2n - 1
we get ,
{ 2 × ( 2n - 1 ) + 3 } : { 5 × ( 2n + 1 ) - 7 }
=>( 4n + 2 - 3 ) : ( 10n - 5 -7 )
=>( 4n - 1) : ( 10n - 12 )
hope it helps you dear !!
thanks !!
thesohan:
I also aim on cracking IIT
Answered by
0
hii friend★★★★★★★
_____________________
your answer is given below
☆☆☆☆☆☆☆☆☆☆☆☆
Given that the ratio is
(2n+3):(5n-7)
now, we have replace the value "n"in to 2n-1
as a result:
2×(2n-1)+3:5×(2n+1)-7
=(4n+2-3):(10n-5-7)
=(4n-1):(10n-12)
......... thanks ......♥♥♥♥
I think it will help you then you mark me brainlist please please please★★★★★★★★★★★★★★★★★★☆☆☆☆♧♧♧♣♣
_____________________
your answer is given below
☆☆☆☆☆☆☆☆☆☆☆☆
Given that the ratio is
(2n+3):(5n-7)
now, we have replace the value "n"in to 2n-1
as a result:
2×(2n-1)+3:5×(2n+1)-7
=(4n+2-3):(10n-5-7)
=(4n-1):(10n-12)
......... thanks ......♥♥♥♥
I think it will help you then you mark me brainlist please please please★★★★★★★★★★★★★★★★★★☆☆☆☆♧♧♧♣♣
Similar questions